Vyandsliefde of geweld: oor die politiek van die historiese Jesus - Scheffler, E. (Faculty of Theology, University of the Free State, 2016)
The fact of the existence of Jesus of Nazareth is recognised in Judaism, Christianity and Islam. Nevertheless these religions are all in one way or another involved in violent conflicts that still ravages the present-day world. Despite making the proposed task more difficult, in this contribution attention will be paid to the historical Jesus’ stance on violence (as contained in the Gospel tradition), our expressed hermeneutical intent being to address contemporary violence, in interpersonal relationships as well as on a global “political” scale (e.g. war). After some remarks on the possibilities and limitations of historical Jesus research, Jesus’ own stance or teaching on violence (e.g. blessed are the peacemakers, loving the enemy and turning the other cheek), as well as his possible involvement in, or opposition to violence in the Palestinian and Roman context of his day will be scrutinised. A “hermeneutical” reflection on the possibility of the appropriation of Jesus’ (non-violent) stance in today’s world concludes the paper. We don’t want to study the historical Jesus, because then we must do the same. – James Murphy O’Conner There is no way to peace, peace is the way. – Mahatma Ghandi You must have breakfast by yourself, lunch with a friend and supper with your enemy. – Nelson Mandela (as president van Suid-Afrika)
Love for the enemy or violence: on the politics of the historical Jesus
Keywords: Love for the enemy; Violence; Historical Jesus; Peace